Approval of First CAR-Ts: Have we Solved all Hurdles for ATMPs?. (17th January 2019) - Seimetz, Diane; Heller, Karl; Richter, Jan
T cells are known as the most potent killer cells of the immune system, designed by nature to prevent unwanted challenges. The first class of therapeutic products harnessing the power of T cells for target-specific treatment of oncological diseases was bispecific antibodies. The first T-cell engaging bispecific antibodies that obtained approval were catumaxomab and blinatumomab 1, 2 . Eight years later, the first chimeric antigen receptor (CAR)-T cells received regulatory approval 3 . CAR-T cells are the cellular interpretation of T-cell engaging therapies and have shown remarkable clinical results. CAR-T cells belong to the regulatory group of advanced therapy medicinal products (ATMPs). Due to the cell-/gene-based complex nature, ATMPs are far more challenging to develop than other, more defined, medicinal products. Despite very encouraging clinical results, there have been many set-backs in the development of ATMPs during the past 20 years. Therefore, the approval of the first two CAR-Ts KYMRIAH and YESCARTA is highly encouraging for the field. In this article we review the current landscape of CAR-Ts as a special class of ATMPs. This comprises the pathway to approval including the use of dedicated regulatory tools and challenges that were faced during the procedure. Furthermore, we highlight important future trends in the field.